Institutional anomie and justification of morally dubious behavior and violence cross-nationally: a multilevel examination - Zito, Rena C. (The Australian and New Zealand journal of criminology, 2019)
This study draws on insights from institutional anomie theory to examine justification of morally dubious behavior and violence cross-nationally. Further, it builds on a burgeoning body of multilevel institutional anomie theory and research on crime-relevant attitudes by considering whether and how individual financial hardship intersects with anomic structural and cultural systems at the national level, acknowledging that individual responses to anomie may be contingent upon experiences with such hardships. Results from multilevel modeling using data from 74,930 World Values Survey respondents in 52 nations, the World Bank, and other organizations provide partial support for the hypotheses. Specifically, conditions of “want amid plenty,” (Bjerregaard & Cochran, 2008a, p. 183) weakened family and education institutions, and monetary fetishism predict justifications cross-nationally. Moreover, economic inequality and individualism moderate the effect of financial hardship on justifications of morally dubious actions and violence, consistent with expectations.